Proximity matrix indicates heterogeneity in the ability to face child malnutrition and pandemics in Brazil: An ecological study - Miguel, Camila Botelho; da Silva, Arianny Lima; Trindade-da-Silva, Carlos Antônio; Abreu, Melissa Carvalho Martins de; Oliveira, Carlo José Freire; Rodrigues, Wellington Francisco (Frontiers in Public Health, 2022)
Background: Among the social inequalities that continue to still surpasses the basic rights of several citizens, political and environmental organizations decisively “drag” the “ghost” of hunger between different countries of the world, including Brazil. The COVID-19 pandemic has increased the difficulties encountered in fighting poverty, which has led Brazil to a worrying situation regarding its fragility in the fight against new pandemics. Objectives: The present study aims to estimate, compare, and report the prevalence of mortality due to child malnutrition among the macro-regions of Brazil and verify possible associations with the outcome of death by COVID-19. This would identify the most fragile macro-regions in the country with the greatest need for care and investments. Methods: The prevalence of mortality was determined using data from the federal government database (DataSus). Child malnutrition was evaluated for the period from 1996 to 2017 and COVID-19 was evaluated from February to December 2020. The (dis)similarity between deaths from malnutrition and COVID-19 was evaluated by proximity matrix. Results: The North and Northeast regions have above average number of deaths than expected for Brazil (p<0.05). A prospective analysis reveals that the distribution of the North and Northeast macro-regions exceeds the upper limit of the CI in Brazil for up to the year 2024 (p<0.05). The proximity matrix demonstrated the close relationship between deaths from COVID-19 and malnutrition for the Northern region followed by the Northeast region. Conclusions: There are discrepancies in frequencies between macro-regions. Prospective data indicate serious problems for the North and Northeast regions for the coming years. Therefore, strategies to contain the outcome of health hazards must be intensified in the macro-regions North and Northeast of the country.